Features of Joint Work of Family and School in Maintaining Children’s Mental Health in War Conditions - Tsurkan, Taisiia (My University, 2022)
The article highlights the importance of the concept of “mental health” and the “interaction between family and school”. Possibilities of art therapy in psychological help to children in the conditions of war are considered. The main directions of art therapy that help protect the mental health of children during the war are described: isotherapy, sand therapy, clay therapy, fairy tale therapy, magic, drama therapy, music therapy. Tips for teachers and parents are outlined on working with children in wartime.
Keywords: “mental health” “interaction between family and school”